2021
DOI: 10.1097/oi9.0000000000000156
|View full text |Cite
|
Sign up to set email alerts
|

Leadership development for orthopaedic trauma surgeons in Latin America: opportunities for and barriers to skill acquisition

Abstract: Introduction: There is growing interest in leadership courses for physicians. Few opportunities are available in global regions with limited resources. This study describes orthopaedic trauma surgeons' desired leadership skill acquisition, opportunities, and barriers to course participation in Latin America.Methods: Latin American orthopaedic trauma surgeons from the Asociación de Cirujanos Traumatólogos de las Americas (ACTUAR) network were surveyed. This survey solicited and gauged the surgeons' level of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(58 reference statements)
0
6
0
Order By: Relevance
“… 33 Moreover, 144 orthopaedic trauma surgeons in Latin America identified professional ethics, crisis management/organizational change management, and high performing team building as the most important topics for leadership development. 34 Finally, a meta-analysis concluded that the ability to initiate structure within a team was the most influential leadership skill for surgeons. 35 The major leadership themes identified in this study were consistent with those previously recognized in other reports.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Moreover, 144 orthopaedic trauma surgeons in Latin America identified professional ethics, crisis management/organizational change management, and high performing team building as the most important topics for leadership development. 34 Finally, a meta-analysis concluded that the ability to initiate structure within a team was the most influential leadership skill for surgeons. 35 The major leadership themes identified in this study were consistent with those previously recognized in other reports.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was completed by 144 orthopedic surgeons from 18 Latin American countries. 10 The results characterized region-specific perspectives, desired competencies, and existing barriers to leadership development participation and formed the basis for a novel Leadership Development Program (LDP) curriculum for Latin American orthopedic trauma surgeons. 10 …”
Section: Introductionmentioning
confidence: 99%
“…9 While the assessment and training of these non-technical skills have become more accessible in high-income countries (HICs), there remains a need for further development and incorporation of these tools into the medical education throughout low-and middle-income countries (LMICs), 1 particularly throughout Latin America. 10 Given the direct association between national income and spending, a significant portion of the care delivered in LMICs is often greatly hindered by the lack of requisite healthcare funding. The burden of disease is greater, advanced technology is limited, the supply of human and material resources is inconsistent, and the healthcare systems remain less integrated than in many HICs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations